A SEER-based prognostic nomogram for early-stage (pT1-2N0M0) tongue squamous cell carcinoma and an observational analysis of postoperative radiotherapy - Dandan Lin; Huling Li; Xing Feng; Yang Zhang; Dandan Tang; Kai Wang (World Journal of Surgical Oncology)
Abstract Background To develop a nomogram for predicting overall survival (OS) and cancer-specific survival (CSS) in patients with postoperative early-stage (pT1-2N0M0) tongue squamous cell carcinoma (TSCC), and to explore the association between postoperative radiotherapy (PORT) and patient survival. Methods Data from 7,637 patients with pT1-2N0M0 TSCC who underwent surgery between 2000 and 2021 were extracted from the SEER database. Patients were randomly divided into a training cohort and a validation cohort in a 2:1 ratio. Prognostic factors were identified via Kaplan-Meier analysis and Cox regression, and a nomogram was constructed. To minimize confounding, propensity score matching (PSM) was used to compare outcomes between patients who received PORT and those who did not. Subgroup and interaction analyses were performed to assess potential effect modifiers. Results Of the 7,637 patients included, 1,336 (17.5%) received PORT. Multivariate Cox analysis identified age, race, marital status, grade, tumor size, lymph node (LN) removed status, and PORT as independent prognostic factors for OS and CSS. The nomogram demonstrated strong predictive performance based on time-dependent ROC curves, concordance indices, calibration plots, and decision curve analyses in both training and validation cohorts. After PSM, PORT remained associated with worse OS and CSS. Subgroup analyses revealed that the association between PORT and poorer OS was most evident in younger patients, married individuals, T1 stage patients, those with smaller tumors, and those without LN removal, with racial disparities also observed. For CSS, this association was more pronounced in married individuals, well-differentiated patients, T1 stage patients, those with smaller tumors, and those without LN removal. Conclusion The SEER-based nomogram provides survival predictions for postoperative pT1-2N0M0 TSCC patients. Although PORT was associated with worse survival in several subgroups, findings should be cautiously interpreted given the observational design and absence of key clinical variables (PNI, LVI, surgical margins). Prospective studies incorporating comprehensive clinicopathological data are warranted to confirm associations and guide individualized PORT decisions in early-stage TSCC patients.